Investigation Methods of Combating Smuggling and Suspicious Trade Through Transport Routes: Ukrainian Case - Kniaziev, Sergii; Verbytskyi, Vitalii; Chernysh, Maryna; Dziubynskyi, Andrii; Kyslyi, Anatolii (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
Smuggling poses a threat both to individuals and to national security. The problem of smuggling is complicated by the constant transformation of criminal schemes, thereby urging the search for appropriate investigation methods of this offense. The aim of the research is to improve the methods of investigation of smuggling through the integration of legislative, international, human, and technical resources. The research employed a doctrinal approach, a statistical method, and a descriptive method. As a result of the research, the Ukrainian legislation on combating smuggling was analysed in the context of European integration. It is noted that the criminalization of smuggling of goods is a welcome innovation, but the legislative framework needs further improvement. The legal basis of Ukraine's international cooperation in the investigation and countering of smuggling has been disclosed. The priority forms of cooperation were determined and directions for further improvement were revealed using the experience of several international initiatives. The value of human capital in combination with the latest technologies in the process of investigating crimes related to smuggling is noted. The obtained conclusions can be useful for regulatory bodies in the context of developing anti-smuggling policies based on identified priority areas.